2022
DOI: 10.1097/njh.0000000000000840
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Educational and Health Care System–Related Issues From Physicians' and Nurses' Perspectives Before Developing a Palliative Care Program Within the Palestinian Health Care System

Abstract: A scarcity in research assessing the palliative care (PC) educational and health care system–related issues has been reported in the Middle East region; the region comprises a wide range of economically diverse countries. Discrepancies across countries have created difficulties in adopting other countries' experiences. This study aimed to assess PC knowledge, attitude, educational needs, and health care system–related issues from physicians' and nurses' perspectives before developing PC services within the Pal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 39 publications
(85 reference statements)
4
9
0
Order By: Relevance
“…A favorable attitude towards the care of dying patients was observed in the current study. Attitude has a pivotal influence on the quality of PC services provided [ 16 ]; this result is in line with previous studies conducted In Muslim countries, including Palestine [ 17 ] and Turkey [ 24 ]; however, the attitude scores are slightly lower than those reported in China Mainland [ 22 ], the USA [ 25 ] and Sweden [ 26 ]; however, it contradicts another study conducted in China which reported negative attitudes among nursing students [ 15 ]. The differences across studies might be attributed to educational, religious and cultural differences across nations [ 27 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…A favorable attitude towards the care of dying patients was observed in the current study. Attitude has a pivotal influence on the quality of PC services provided [ 16 ]; this result is in line with previous studies conducted In Muslim countries, including Palestine [ 17 ] and Turkey [ 24 ]; however, the attitude scores are slightly lower than those reported in China Mainland [ 22 ], the USA [ 25 ] and Sweden [ 26 ]; however, it contradicts another study conducted in China which reported negative attitudes among nursing students [ 15 ]. The differences across studies might be attributed to educational, religious and cultural differences across nations [ 27 ].…”
Section: Discussionsupporting
confidence: 85%
“…In Palestine, little effort has been made regarding PC education, and most of efforts have focused on nurses and physicians working in hospitals [ 16 ]. Only one study [ 17 ] conducted in Palestine in 2015 examined 141 nursing students’ attitudes toward EoLC; the results reported low levels of attitude towards caring for dying patients and their families.…”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer is the second most commonly diagnosed cancer in Palestine, comprising 11.4% of the total cancers ( 58 ). The fragile Palestinian HCS, shortage of healthcare professionals ( 59 ), and limited resources impede achieving optimal cancer services and meeting the needs of cancer patients, including lung cancer ( 60 , 61 ). Furthermore, Palestinian patients with lung cancer are unfortunately diagnosed at a late stage, and they experience shortness of breath, coughing up blood, and severe chest pain ( 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…They coordinate care for patients, their families, and other healthcare workers [ 11 ]. They are responsible for practically all bedside care; therefore, they should have adequate knowledge and training in PC to fulfil the demands of the patients [ 12 ]. Appropriate knowledge and training also aid nurses in efficiently communicating with patients and their families and easing their suffering [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%